OF MIRACLES AND METAPHYSICS: A PENTECOSTAL‐CHARISMATIC AND PROCESS‐RELATIONAL DIALOGUE. Issue 2 (28th May 2013) - Reichard, Joshua D.
Abstract: This article is comprised of a dialogue between Pentecostal‐Charismatic and Process‐Relational theologies on the perennial issue of miracles. The language of supernaturalism, widely employed by Pentecostal‐Charismatic theologians, is contrasted with the metaphysical naturalism of Process‐Relational theology; it is proposed that a philosophically and scientifically sensitive theology of miracles is possible through a synthesis of both traditions. Themes such as nonmaterialism over materialism, spiritual experience, and prayer for healing miracles are explored. A theology of miracles, mutually informed by both Pentecostal‐Charismatic and Process‐Relational theologies, may focus less on whether or not miracles are possible, but instead focus more on what kind of miracles human beings might value most. By mutually engaging a theology of nonsupernatural, metaphysically grounded miracles, Pentecostal‐Charismatic and Process‐Relational theologians may collaborate to establish the groundwork for creative scientific enterprises, especially in the non‐Western world where Pentecostalism continues to experience its most rapid growth, Such perspectives may eventually lead to cutting‐edge discoveries about the fundamental nature of, and God's interaction with, reality itself. Implications for future research are proposed.